Development of a Genetics Textbook Integrating Local Observational Case Study Assignments to Support Critical Thinking and Problem-Solving Skills - Narsan, Vifty Octanarlia; Ummah , Allydya Chotibatul; Utami, Rhodiya Kamalia; Putri, Rahayu Dian Eka (Al Jahiz, 2025)
Students’ understanding of genetic concepts is often hindered by the abstract and complex nature of the material, particularly because genetic processes occur at the molecular level and cannot be directly observed. Based on a preliminary survey conducted in the Biology Education Program at UIN Jurai Siwo Lampung, most students perceive genetics as a difficult and overly theoretical subject. This study aims to develop a genetics textbook integrated with local case study observation assignments to enhance students’ critical thinking and problem-solving skills. The research employed the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation), involving expert validation by content and media specialists, as well as a limited trial with students. The instruments used included validation sheets and student response questionnaires, which were analyzed quantitatively using a Likert scale and percentage of achievement. Validation results showed that the product received a score of 92% from the content expert and 85.3% from the media expert, both categorized as “Highly Appropriate.” The trial with students yielded an average score of 83.9%, falling under the “Highly Practical” category. The study concludes that the genetics textbook based on local case studies is valid and practical for helping students understand abstract genetic concepts in a contextual manner, while also supporting the development of critical thinking and problem-solving skills.